PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMA DARUSSALAM - Nur Hidayati; Sayu Ida Sadatus Syarifah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
The objectives of this study are 1). To determine the effect of the Principal's Managerial Skills on Teacher Performance in SMA Darussalam Blokagung Banyuwangi, 2). To find out how much influence the principal's managerial skills have on teacher performance in SMA Darussalam Blokagung Banyuwangi. This research uses quantitative descriptive method with product moment technique in data validity test and to find data reliability using alpha formula, while in hypothesis testing using F test and T test using regression models. The population of this study were 42 SMA Darussalam Blokagung Banyuwangi teachers. After analyzing that it was found that the Principal Managerial Skills were very influential on Teacher Performance in SMA Darussalam Blokagung Banyuwangi as evidenced by the results of data analysis of 67.7% while the remaining 32.3% was influenced by other variables.